Live and/or sleep high: train low, using normobaric hypoxia - Richalet, J. P.; Gore, C. J. (Scandinavian Journal of Medicine & Science in Sports, 2008)
The increase in oxygen transport elicited by several weeks of exposure to moderate to high altitude is used to increase physical performance when returning to sea level. However, many studies have shown that aerobic performance may not increase at sea level after a training block at high altitude. Subsequently, the concept of living high and training low was introduced in the early 1990s and was further modified to include simulated altitude using hypobaric or normobaric hypoxia. Review is given of the main studies that have used this procedure. Hematological changes are limited to insignificant or moderate increase in red cell mass, depending on the "dose" of hypoxia. Maximal aerobic performance is increased when the exposure to hypoxia is at least over 18 days. Submaximal performance and running economy have been found increased in several, but not all, studies. The tolerance (fatigue, sleep, immunological status, cardiac function) is good when the altitude or simulated altitude is not higher than 3000 m. Virtually no data are available about the effect of this procedure upon anaerobic performance. The wide spread of these techniques deserves further investigations.